A case study of odour nuisance evaluation in the context of integrated urban planning. (1st May 2018) - Badach, Joanna; Kolasińska, Paulina; Paciorek, Małgorzata; Wojnowski, Wojciech; Dymerski, Tomasz; Gębicki, Jacek; Dymnicka, Małgorzata; Namieśnik, Jacek
Abstract: Odour nuisance poses a serious problem in many urban areas, yet its evaluation and mitigation is often omitted in the urban planning process. By identifying its range and spatio-temporal variations, it could be taken into consideration by planners in urban development strategies and land use decisions. The aim of the study was to present the application of odour evaluation techniques in the improvement of the quality of life in the built environment. The problem of odours is discussed in regard to human health, social aspects and current practices in the management of spatial development. The application possibilities of field olfactometry are demonstrated based on a case study of a municipal landfill which is a major source of odour nuisance for the adjacent areas. The results of odour nuisance measurements were field olfactometry combined with topographical and meteorological data. Using dispersion modelling (non-steady-state Lagrangian Gaussian puff model CALPUFF with dedicated meteorological pre-processor CALMET) it was possible to calculate odour concentrations and to place the measured odour concentrations in a specific spatial context. The obtained results were juxtaposed with local development strategies and discussed in the context of environmental-based planning. We suggest that odour evaluation and dispersion modelling are valid tools in managing the dynamics of urban growth. Graphical abstract: Image 1 Highlights: Odours, a specific type of air pollution in urban areas, were studied. A case study of a residential area adjacent to a municipal landfill was presented. Odour nuisance can be evaluated using field olfactometry and dispersion modelling. The obtained results were translated into a specific urban context. Development strategies for local spatial planning were formulated.